A Very Rare Case of Pulmonary Lepidic Adenocarcinoma at a Young Age Man - Kristy, Anastasia; Putra, Wayan (Universitaas Brawijaya, 2024)
Introduction: Lung cancer remains one of the higher prevalence of cancer and leading cause of death in the world. Smoking and genetic factors are two important etiologies in lung cancer. Adenocarcinoma is the most common type of non-small cell lung carcinoma. Lepidic predominant adenocarcinoma is one type of adenocarcinoma that has a good prognosis. Case Illustration: A 24-year-old male came with chronic cough and chest pain. He had a history of smoking and no prior family history of cancer. Plain chest Xray and Thorax computed tomography (CT) showed pleural effusion and presence of lung mass with suggestion of bone and liver involvement, respectively. The cytology from pleural effusion and bronchial lavage initially found no malignancy cell. Later thoracostomy biopsy and pathology study suggested lepidic adenocarcinoma. Discussion: Lung cancer is still one of the leading causes of death in men. Even though rarely found in young male, patients with a history of smoking or genetic factor with clinical manifestation suggestive chronic respiratory condition with weight loss should be suspected of the diagnosis. Adenocarcinoma, as the most common non-small cell lung carcinoma, could be later divided into several subtypes. Lepidic adenocarcinoma is distinguished by the pathology finding of a large invasion focus of stromal, lymphatic, vascular, or pleural space. Considered one of the most favorable, lepidic predominant adenocarcinoma has a very high rate of 5 year survival when diagnosed early and responds well to lobe resection. Advanced state however has poor outcome due to limited choice of therapy. Promising trial of targeted chemotherapy have been reported and could improve outcome in the future. Conclusion: Lung cancer in young male is a rare disease but should be suspected in those with chronic cough, chest pain and weight loss. The history of smoking and family history are crucial for this suspicion. Lepidic predominant adenocarcinoma has a good prognosis when diagnosed early. Studies in the future could enhance overall survival in these patients.